2022
DOI: 10.3389/fendo.2022.924841
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Options for Radioiodine-Refractory Differentiated Thyroid Carcinoma: Recent Advances, Challenges, and Road Ahead

Abstract: Radioiodine-refractory differentiated thyroid cancer (RAIR-DTC), though uncommon, presents a considerable therapeutic challenge with poor long-term outcomes. Currently, tyrosine kinase inhibitors are the mainstay of treatment for advanced RAIR-DTC patients. However, these agents are associated with a multitude of adverse events with resultant deterioration in the quality-of-life of the patients. Targeted theranostic approaches with radiolabelled integrin binders and fibroblast activation protein- (FAP)-inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The present study represents the most comprehensive effort to date in consolidating existing evidence on the benefits of RAI therapy in intermediate‐risk PTC over NOI follow‐up. This is particularly important given the context of a growing body of literature discouraging indiscriminate use of RAI therapy in low‐risk PTC as it does not confer significant improvement in disease‐specific mortality and tumour recurrence rates, particularly in patients with small primary tumours 8–11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study represents the most comprehensive effort to date in consolidating existing evidence on the benefits of RAI therapy in intermediate‐risk PTC over NOI follow‐up. This is particularly important given the context of a growing body of literature discouraging indiscriminate use of RAI therapy in low‐risk PTC as it does not confer significant improvement in disease‐specific mortality and tumour recurrence rates, particularly in patients with small primary tumours 8–11 …”
Section: Discussionmentioning
confidence: 99%
“…ATA guidelines do not routinely recommend RAI therapy for low‐risk PTC 5 . There is a growing body of evidence that has demonstrated no significant long‐term benefit of RAI use, particularly for low‐risk disease with small primary tumours 8–11 . However, in view of conflicting observational data, the role of RAI in intermediate‐risk PTC remains a topic of ongoing discussion.…”
Section: Introductionmentioning
confidence: 99%
“…5%–15% of DTCs and 50% of metastatic DTCs progress to RAIR, and overall survival is significantly reduced, less than 10% at 10 years ( Lorusso et al, 2023 ). Treatment options for symptomatic, rapidly progressing, inoperable locally advanced/extensive metastatic RAIR-DTC are limited to FDA-approved tyrosine kinase inhibitors (TKIs) ( Satapathy and Bal, 2022 ). However, the use of TKIs is associated with a variety of adverse events, such as cardiotoxicity, hematologic toxicity, fatigue, skin reactions, etc., which can limit patients’ daily activities, reduce compliance, and lead to high treatment withdrawal rates ( Chrisoulidou et al, 2015 ).…”
Section: Thyroid Cancer Treatment and Challengesmentioning
confidence: 99%
“…A long-term study showed that 10- and 15-years survival rate in RAIR-DTC were much lower than those of DTC patients with RAI uptake (10% vs 56% and 6 vs 45%, respectively) ( 9 ). RAIR patients represent a great therapeutic challenge due to the limited alternative therapeutic options ( 12 , 13 ). Therefore, understanding non-radioiodine avidity and identification of risk factor that help in early prediction of RAIR-DTC is of great clinical importance in avoiding unnecessary RAI therapy and help in the decision of subsequent feasible targeted therapy.…”
Section: Introductionmentioning
confidence: 99%